Teaching maths outside the classroom: does it make a difference?. Issue 1 (2nd January 2019) - Otte, Camilla R.; Bølling, Mads; Elsborg, Peter; Nielsen, Glen; Bentsen, Peter
ABSTRACT: Background: An emerging field of research indicates that the use of learning environments other than the classroom can improve pupils' academic achievement in several subjects, including their skills in mathematics. Purpose: The aim of this study was to investigate the association between Education Outside the Classroom (EOtC) and pupils' skills in mathematics. Methods: This explorative, quasi-experimental study involved schoolchildren (aged 9–13 years) from 15 Danish public schools who participated in EOtC over the course of a school year. The mathematical skills of pupils from 23 EOtC maths intervention classes ( n =421) and 12 EOtC non-maths comparison classes ( n =198) were measured at the start and end of the 2014–2015 school year. Results: Both groups showed improved maths skills; however, we found no significant difference between the EOtC maths and the comparison groups. Conclusion: The results indicate that, in this explorative study, moving maths teaching outside the classroom neither harmed nor improved pupils' mathematical skills. These results and implications for research are discussed.